A case report: cccDNA and pgRNA remain positive in liver tissue in a chronic hepatitis B patient with functional cure - Xu, Wenxiong; Luo, Qiumin; Zhang, Yeqiong; Xie, Chan; Peng, Liang (Frontiers in Medicine, 2024)
Hepatitis B surface antigen (HBsAg) seroclearance is recommended as the ideal endpoint for nucleos(t)ide analogues (NAs) treatment. Functional cure of chronic hepatitis B (CHB) is defined as undetectable serum hepatitis B virus (HBV) deoxyribonucleic acid and serum HBsAg. We report a functional cure case of CHB with hepatocellular carcinoma (HCC) family history after long-term NAs therapy. Both HBV covalently closed circular deoxyribonucleic acid (cccDNA) and pregenomic ribonucleic acid (pgRNA) are remaining positive in liver tissue of the case, indicating that sterilizing cure is not achieved, although functional cure has been achieved for over seven years. This case highlights the importance of active surveillance of HBV cccDNA and pgRNA for sterilizing cure and risk of HCC.